Screening for Syphilis in Cases of Suspected Gonorrhea and Chlamydia Infections - Kumara V. Nibhanipudi MD, FAAP, FAAEM; Kenneth Cody MD (SAGE Publishing, 2017)
Background . In all cases of suspected sexually transmitted infections (STIs), it has been routine practice to screen for syphilis with a blood sample. The incidence of syphilis seems to be lower than that of commonly screened STIs. Objective . The objective of our study was to determine whether it is cost-effective to screen for syphilis with serological testing in cases of suspected gonorrhea and chlamydia infections. Hypothesis . Our hypothesis is that it is not cost-effective to screen for syphilis in cases of presumed gonorrhea and chlamydia infections. Methods . Our study is a New York Medical College institutional review board-approved retrospective study. During the period January 2004 to August 12, 2006, the laboratory work of all patients tested for gonorrhea and chlamydia in our emergency department was reviewed. The charts were reviewed for the following tests: gonorrhea DNA probe, chlamydia DNA probe, and syphilis IgG (immunoglobulin G)/RPR (rapid plasma reagin). The results of these tests were obtained and analyzed. Results . The total number of patients screened for gonorrhea and chlamydia during this period was 196. Seventy-eight patients tested positive for gonorrhea and chlamydia. All these 78 patients, tested negative for syphilis. The overall prevalence of positivity for STIs was 39.8% (78/196). The prevalence of chlamydia alone was 85.9% (67/78) and gonorrhea alone was 7.69% (6/78). The prevalence of combined both chlamydia and gonorrhea was 6.4% (5/78). Statistics . We used online SILICO 2 × 4 Fisher exact test. By comparing positive and negative results of serology RPR, GC, and chlamydia trap, the resultant 2-tailed P value is <.0001, which is statistically significant. Conclusions . Per our study, the yield of syphilis testing was negligible. It may not be cost-effective to screen for syphilis in cases of STIs such as gonorrhea and chlamydia.